Peer Support during Student Teachers’ Practicum: A Case Study using a Web 2.0 Community on the Cloud - Κώστας Απόστολος Αθανάσιος; Σοφός Αλιβίζος (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2017)
The availability of emerging technologies in teacher’s education leads to new social arrangements to coordinate the learning experience at the institutional level and the practical experience at the school level, aiming at the enhancement of teachers’ preparation programs. In this context, this paper presents results from a case study taken place at the Department of Primary Education, University of the Aegean, Greece. Specifically, research focused on the impact of a cloud-based Web 2.0 online community during practicum and the perceptions that students formed as members of this community during the semester. Results highlights the role of the community as a mechanism for peer support and cooperation for student teachers during their internship in schools.